Stress Field in the 2016 Kumamoto Earthquake (M 7.3) Area. Issue 3 (2nd March 2019) - Yu, Zhiteng; Zhao, Dapeng; Li, Jiabiao; Huang, Zhouchuan; Nishizono, Yukihisa; Inakura, Hirohito
Abstract: We used 1‐D and 3‐D velocity models to determine focal mechanism solutions (FMSs) of 349 crustal earthquakes ( M 2.7–7.3) and stress tensors in the source area of the 2016 Kumamoto earthquake ( M 7.3) that occurred on the Futagawa‐Hinagu fault zone in Kyushu, Southwest Japan. There are some differences in the FMSs determined with the 1‐D and 3‐D velocity models. The use of the 3‐D velocity model leads to better results of stress tensors, which are determined by inverting the FMSs. The orientation of the minimum stress ( σ 3 ) axis is more accurately determined, which trends NNW‐SSE to N‐S nearly horizontally. In contrast, the axes of the maximum and intermediate stresses ( σ 1 and σ 2 ) trend WSW‐ENE to E‐W with wide ranges. Significant spatiotemporal variations of the stress field are revealed in the Kumamoto source zone, indicating a small magnitude of deviatoric stress. The friction coefficient of the faults is estimated to be relatively small ( 0.4), indicating that the seismogenic faults in central Kyushu are weak. The fault weakening may be caused by fluids beneath the source area and arc magma under the nearby Aso active volcano. Key Points: Focal mechanism solutions and stress tensors in the 2016 Kumamoto earthquake area are determined with a 3‐D velocity model The 3‐D velocity model leads to better results of stress tensors Seismogenic faults in the source area are weak due to the effect of arc magma and fluids